Obraz obecności wojsk amerykańskich w Polsce na łamach prasy lokalnej, regionalnej i ogólnopolskiej w 2017 r. – raport z badań - Bartoszewicz, Mateusz (Historia i Polityka, 2020)
The objective of the studies was to find answers to the research question: how the issue of US military presence in Poland was reported in selected press titles on different levels (local, regional, and national) in 2017? The author, using a framing analysis, adopts an idiographical perspective which objective is to research an unexplored (so far) part of Polish press discourse. This specific part has the exceptional – social, political and military – significance that binds with the presence of thousands US soldiers being stationed in Poland.